Effectiveness and Reflection: Short Video Marketing Explodes the Market of Domestic Literary Films-- A Case Study of Return to Dust - Wei, Qu; Haiyan, Chen (Mandarinable: Journal of Chinese Studies, 2000)
The audience spontaneously acted as "tap water" to initiate short video marketing, successfully triggering the box office market of the domestic literary film Return to Dust, making it a typical case of the film industry with great significance. The "tipping point" of the film at the box office is not only due to the combined effect of the dissemination of the short video of secondary creation and the live streaming of the traffic stars but also due to the topic sense created by the spiritual core of the film itself. At the same time, it benefits from the cross-media communication environment created by the UGC (user-generated content) model and the precise push of big data. With the combined force of these three parties, a breakthrough effect was formed, creating a "box office miracle" for domestic literary films. The short video explosion of the domestic literary film market is quite enlightening: only by taking quality as the core to create excellent films and taking traffic as a gripper to promote film cross-media marketing, can we get out of the film development road of "traffic + quality" with Chinese characteristics.